2017
DOI: 10.1080/15389588.2017.1341630
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pedestrian age and gender on spatial and temporal distribution of pedestrian crashes

Abstract: This research reveals that temporal and spatial distributions of vehicle-pedestrian crashes vary for different pedestrian age groups and genders. Therefore, specific safety measures should be in place during high crash times at different locations for different age groups and genders to increase the effectiveness of the countermeasures in preventing and reducing vehicle-pedestrian crashes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…The predictions based on these two types of data should be improved using other factors, such as individual characteristics and crash attributes. The findings of this study are in line with those of Onieva-García et al [63], Toran Pour et al [64], Park and Ko [65], Li and Fan [44], and Kim et al [66], who confirmed the significant roles of age and gender in pedestrian-related crashes and deaths. Several studies also confirmed the effects of bus involvement on the risks of injury and death of pedestrians (e.g., [67][68][69]), which indicates the significant role of crash attributes in the prediction of PDRC.…”
Section: Variable Significancesupporting
confidence: 92%
“…The predictions based on these two types of data should be improved using other factors, such as individual characteristics and crash attributes. The findings of this study are in line with those of Onieva-García et al [63], Toran Pour et al [64], Park and Ko [65], Li and Fan [44], and Kim et al [66], who confirmed the significant roles of age and gender in pedestrian-related crashes and deaths. Several studies also confirmed the effects of bus involvement on the risks of injury and death of pedestrians (e.g., [67][68][69]), which indicates the significant role of crash attributes in the prediction of PDRC.…”
Section: Variable Significancesupporting
confidence: 92%
“…Moreover, detailed information on accident dynamics are missing, as there are no information on the role played by pedestrians. A literature review highlighted how personal characteristics, attitudes, and habits (e.g., age, cognitive abilities, distraction, lack of caution, use of cell phones) can increase the risk of pedestrian accidents [76][77][78]. Hence, the inclusion of the above-mentioned factors in a new dataset will help to improve our study findings.…”
Section: Discussionmentioning
confidence: 95%
“…Demetriades et al [32] indicated that the degree of severity differs by pedestrian age. In addition, a recent study by Toran Pour et al [15] showed that the temporal and spatial distributions of pedestrian-involved accidents vary according to the age of the pedestrian.…”
Section: Characteristics Of the Built Environmentmentioning
confidence: 99%
“…This is because the physical characteristics and behaviors of pedestrians in urban areas, along roads, vary depending on their age. Consequently, this makes it necessary to examine the association between the severity of the injury and the built environment in relation to pedestrian age, to provide more efficient and effective policy recommendations [15].…”
Section: Introductionmentioning
confidence: 99%